Bypass Diodes for Improving Solar Panel Performance - Fadliondi Fadliondi; Haris Isyanto; Budiyanto Budiyanto (Institute of Advanced Engineering and Science, 2018)
The ouput power of solar panel that decreased due to shading has been improved using bypass diode method. The placement of bypass diodes increased the output current and power. New peaks and maximum powerpoints on the current-svoltage characteristics and power-voltage characteristics were observed. Without bypass diodes, the maximum output power was only around 50 W. After placing bypass diodes, the first peak around 115 W and second peak around 150 W appeared at voltage of around 31 V and 40 V, respectively.